2021
DOI: 10.3906/sag-2103-127
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system involvement in patients with acute myeloid leukemia

Abstract: Background/aim To evaluate the incidence, clinical features, risk factors, and prognosis of central nervous system (CNS) involvement in patients with acute myeloid leukemia (AML). Materials and methods All AML patients who were admitted to Hacettepe University hospital between 2000 and 2021 were evaluated. The medical records of 548 AML cases were retrospectively analyzed. Results The frequency of CNS involvement was 2.4% (n = 13) at diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 0 publications
6
14
0
Order By: Relevance
“…In our study, we confirmed the association of CNS pos status with lymphadenopathy, a higher percentage of BM blasts, WBC ≥30 � 10 9 /L, and presence of the monocytic phenotype in asymptomatic patients, which is in line with previous reports. [1][2][3][4][5][13][14][15]17 Besides, our patient group also had a higher…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…In our study, we confirmed the association of CNS pos status with lymphadenopathy, a higher percentage of BM blasts, WBC ≥30 � 10 9 /L, and presence of the monocytic phenotype in asymptomatic patients, which is in line with previous reports. [1][2][3][4][5][13][14][15]17 Besides, our patient group also had a higher…”
Section: Discussionmentioning
confidence: 53%
“…Our patients were selected according to the risk factors proposed by data reported in the literature. [1][2][3][4][5][13][14][15][16][17][18][19] Most patients in our selected series were asymptomatic. The overall incidence of CNS involvement in the whole group was 12.6%, which is higher that reported in other publications.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations